Sinonasal Outcome Test (Snot-22) Scores as a Predictor of Outcome in Patients Undergoing Functional Endoscopic Sinus Surgery (FESS) for Chronic Rhinosinusitis (CRS) at a Tertiary Care Centre in Eastern Nepal - Thakur, Sanjeev Kumar; Adhikari, Apar; Khanal, Tekendra; Ray, Rajesh Kumar; Ghimire, Nisha (Medical Journal of Eastern Nepal, 2023)
Background: Sino nasal outcome test (SNOT) is a subjective tool in which both nasal and health-related symptomatic improvements are assessed in cases of Chronic Rhinosinusitis (CRS). We aim to report the demography of CRS patients and magnitude of symptoms, along with its improvement over time after the surgery, using SNOT questionnaire.Methods: A hospital based prospective, descriptive study was done in 35 patients with medically refractory CRS cases who underwent Functional endoscopic sinus surgey (FESS), over one year. All patients were routinely examined the 1st week, the 4th week, and 3 months after surgery.The cases were assessed preoperatively and then after surgery, using the Sino-nasal Outcome Test-22 (SNOT-22) questionnaire, for a maximum of 3 months period. The results were expressed in number and percentage. Mean and standard deviation were used to describe the findings and compare the initial and follow up values. Association between preoperative and postoperative symptoms was analyzed using paired sample t-test and p value less than 0.05 were considered significant.Results: The age range was 14-64 years, with a mean age of 33.11 ± years. 12(34.28%) were male and 23(65.71%) were female. Polyps were present in 12 (34.28%). 23 (65.71%) cases were without polyp. The mean SNOT score overall preoperatively was 33.94±SD, while postoperative SNOT score was 19.05±SD. There was a significant improvement in nasal, ear and facial symptoms, quality of life symptoms and psychological symptoms.Conclusion: There was an overall improvement in all the symptoms postoperatively, though the Cough and dizziness improvement was not statistically significant.